Through mobility we conquer : the mechanization of U.S. Cavalry - Hofmann, George F. (UPSO - University Press of Kentucky E-Books., 2006)
The U.S. Cavalry, which began in the nineteenth century as little more than a mounted reconnaissance and harrying force, underwent intense growing pains with the rapid technological developments of the twentieth century. From its tentative beginnings during World War I, the eventual conversion of the traditional horse cavalry to a mechanized branch is arguably one of the greatest military transformations in history. Through Mobility We Conquer recounts the evolution and development of the U.S. Army's modern mechanized cavalry and the doctrine necessary to use it effectively, and explores the d.